Doug Gilbert: Little Giant in the World of Sport: Sports Comparison Study GDR-Canada --- Eberhard Bock et al.: A Wonderful Experience: Spartakiad Games in the GDR - Roland Grimes (GDR Bulletin, 1977)
Toronto: Kontakt Presse, 1976. 64 p. Dresden: Verlag Zeit im Bild DDR, 1975. 30 p.